Pengaruh Kompensasi Finansial Dan Nonfinansial Terhadap Kepuasan Kerja Dan Kinerja Karyawan Pada PT. Cindara Pratama Lines Balikpapan - Arkas Viddy; Gunadi Gunadi; Syarifah Fahma Nida Aulia (Politeknik Negeri Samarinda, 2020)
The Influences of Financial Compensation and Non-Financial Compensation on Working Satisfaction and Working Performance in PT. Cindara Pratama Lines Balikpapan. The purpose of this research is to identify the influences of Financial Compensation and Non-Financial Compensation on Working Satisfaction and Working Performance in PT. Cindara Pratama Lines Balikpapan. The respondents of this research are 50 employees of PT. Cindara Pratama Lines Balikpapan. All of the questioners collected are examined to ensure all the items are valid and reliable. Path Analysis instrument been used for analyzing the research. Smart PLS and SPSS Software would be used for examining the path coefficient. The result of this research are : 1. Financial Compensation (X1) has a significant effect on Working Satisfaction (Y1), 2. Financial Compensation (X2) has a significant effect on Working Performance (Y2), 3. Non-Financial Compensation (X2) has a significant on Working Satisfaction (Y1), 4. Non-Financial Compensation (X2) has a significant effect on Working Performance (Y2), and 5. Working Satisfaction (Y1) has a significant effect on Working Performance (Y2) in PT. Cindara Pratama Lines Balikpapan